Formation of professional training of future teachers of physical education in the context of the implementation of inclusive education - Ибрагим, Кайрат; Alkaya, Ercan; Tuyakbaeva, Meruert; Nuralieva, Artyk; Belegova, Aliya (Pedagogy and Psychology, 2023)
Abstract In this article, the meaning of the concepts “Inclusion”, “Inclusive education”, “and Accessible environment” based on the analysis of scientific and pedagogical, psychological, special methodological literatures are been defined. The analysis of the possibilities of professional training of future teachers of physical education in the context of the implementation of inclusive education in the higher education institution was carried out. In addition, future teachers of physical education are expected to know the age and psychological characteristics of students with various pathologies in the process of pedagogical practice, the mechanisms of constructive pedagogical interaction of all subjects of the educational environment. The problems of adaptation of children with special educational needs in the social environment, “inclusion” in school life through self-government, the formation of conditions for receptive “tolerance” from the position of participants in an inclusive space and career guidance work are considered. The survey of future specialists were been conducted based on the results of an empirical study.